An Introduction to the Callithrix Genus and Overview of Recent Advances in Marmoset Research. (22nd December 2021) - Malukiewicz, Joanna; Boere, Vanner; de Oliveira, Maria Adélia Borstelmann; D'arc, Mirela; Ferreira, Jéssica V A; French, Jeffrey; Housman, Genevieve; de Souza, Claudia Igayara; Jerusalinsky, Leandro; R de Melo, Fabiano; M Valença-Montenegro, Mônica; Moreira, Silvia Bahadian; et al.
Abstract: We provide here a current overview of marmoset ( Callithrix ) evolution, hybridization, species biology, basic/biomedical research, and conservation initiatives. Composed of 2 subgroups, the aurita group ( C aurita and C flaviceps ) and the jacchus group ( C geoffroyi, C jacchus, C kuhlii, and C penicillata ), this relatively young primate radiation is endemic to the Brazilian Cerrado, Caatinga, and Atlantic Forest biomes. Significant impacts on Callithrix within these biomes resulting from anthropogenic activity include (1) population declines, particularly for the aurita group; (2) widespread geographic displacement, biological invasions, and range expansions of C jacchus and C penicillata ; (3) anthropogenic hybridization; and (4) epizootic Yellow Fever and Zika viral outbreaks. A number of Brazilian legal and conservation initiatives are now in place to protect the threatened aurita group and increase research about them. Due to their small size and rapid life history, marmosets are prized biomedical models. As a result, there are increasingly sophisticated genomic Callithrix resources available and burgeoning marmoset functional, immuno-, and epigenomic research. In both the laboratory and the wild, marmosets have given us insight into cognition, social group dynamics, human disease, and pregnancy. Callithrix jacchus and C penicillata are emerging neotropical primate models for arbovirus disease, including Dengue and Zika. Wild marmoset populations are helping us understand sylvatic transmission and human spillover of Zika and Yellow Fever viruses. All of these factors are positioning marmosets as preeminent models to facilitate understanding of facets of evolution, hybridization, conservation, human disease, and emerging infectious diseases.